2018
DOI: 10.1038/s41419-018-1192-7
|View full text |Cite
|
Sign up to set email alerts
|

Calcimimetic restores diabetic peripheral neuropathy by ameliorating apoptosis and improving autophagy

Abstract: Decreased AMPK-eNOS bioavailability mediates the development of diabetic peripheral neuropathy (DPN) through increased apoptosis and decreased autophagy activity in relation to oxidative stress. Schwann cells are responsible for maintaining structural and functional integrity of neurons and for repairing damaged nerves. We evaluated the neuro-protective effect of cinacalcet on DPN by activating the AMPK-eNOS pathway using db/db mice and human Schwann cells (HSCs). Sciatic nerve of db/db mice was characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 32 publications
5
34
0
Order By: Relevance
“…LC3 and P62 are the main proteins regulating cell autophagy that were down-regulated in the sciatic nerves of diabetic mice and high glucose-treated RSC96 cells vs. the normal control group in the present study, which suggests the dysregulation of cell autophagy. In line with our findings, Chung et al (13) revealed that the LC3-II/LC3-I ratio and beclin-1 were decreased in the sciatic nerves of db/db mice compared with db/m mice. Similarly, high glucose induced the decreases in beclin-1 expression, LC3-II/LC3-I ratio, and LC3 punctate in human Schwann cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…LC3 and P62 are the main proteins regulating cell autophagy that were down-regulated in the sciatic nerves of diabetic mice and high glucose-treated RSC96 cells vs. the normal control group in the present study, which suggests the dysregulation of cell autophagy. In line with our findings, Chung et al (13) revealed that the LC3-II/LC3-I ratio and beclin-1 were decreased in the sciatic nerves of db/db mice compared with db/m mice. Similarly, high glucose induced the decreases in beclin-1 expression, LC3-II/LC3-I ratio, and LC3 punctate in human Schwann cells.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the LC3-II/LC3-I ratio was decreased in the sciatic nerves of diabetic mice vs. normal mice. In line with this, the LC3-II/LC3-I ratio and number of LC3 punctate were reduced in human Schwann cells grown in a highglucose medium in comparison with those grown in a lowglucose medium (13). Qu et al (14) also revealed that there were fewer autophagosomes in immortalized rat Schwann cell 96 (RSC96) cells and primary rat Schwann cells under high-glucose conditions than under control conditions.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…RSC 96 cells, which maintain the attributes of SCs, are cultivated in medium with high glucose (HG) to simulate SCs in DPN mice . In addition, SCs damage induced by HG includes morphological changes, for instance swelling and vacuolation, leading to destruction of organelles . This process is also accompanied by the occurrence of intracellular autophagy and apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…The International Diabetes Federation has estimated that 415 million people have been diagnosed with DM worldwide and anticipates an increase of up to 640 million by 2040 (1). Diabetic neuropathy (DN) is one of the most common diabetic complications and is characterized by complex changes in functional and sensorimotor parameters (2). The pathophysiology of DN involves a complex cascade of specific interrelated mechanisms (3,4).…”
Section: Introductionmentioning
confidence: 99%